2021
DOI: 10.1002/ctpp.202100073
|View full text |Cite
|
Sign up to set email alerts
|

Obliquely propagating ion‐acoustic shock waves in a degenerate quantum plasma

Abstract: A theoretical investigation has been carried out on the propagation of non-linear ion-acoustic shock waves (IASHWs) in a magnetized degenerate quantum plasma system composed of inertial non-relativistic positively charged light and heavy ions, inertialess non-relativistically or ultra-relativistically degenerate electrons and positrons. The reductive perturbation method has been employed to derive the Burgers' equation. It has been observed that under consideration, our plasma model supports only positive pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Landau damping and the kinematic viscosity among the plasma species are the primary reasons for the formation of shock profile associated with electrostatic waves [30][31][32]. The existence of the external magnetic field is considered to be responsible for changing the configuration of the shock profile [33]. Sabetkar and Dorranian [30] examined the effects of external magnetic field on the formation of the DA solitary waves in the presence of non-thermal plasma species, and found that the amplitude of solitary wave increases with the increase in the value of oblique angle.…”
Section: Introductionmentioning
confidence: 99%
“…Landau damping and the kinematic viscosity among the plasma species are the primary reasons for the formation of shock profile associated with electrostatic waves [30][31][32]. The existence of the external magnetic field is considered to be responsible for changing the configuration of the shock profile [33]. Sabetkar and Dorranian [30] examined the effects of external magnetic field on the formation of the DA solitary waves in the presence of non-thermal plasma species, and found that the amplitude of solitary wave increases with the increase in the value of oblique angle.…”
Section: Introductionmentioning
confidence: 99%